Development of Sybr Green 1 Based Real-Time Polymerase Chain Reaction for Detection and Differentiation of Infectious Bursal Disease Virus - Hamzah, Hairul Aini (2005)
The current available method to differentiate very virulent and vaccine strains of infectious bursa1 disease virus (IBDV) is by restriction fragment length polymorphism of VP2 gene. However, this method is time consuming, errorproned and less sensitive. The newly developed TaqMan real-time PCR is very sensitive but not suitable for routine test as it is expensive. Additionally, the application of the assay in detecting very virulent and vaccine strains of IBDV has not been reported. In this study the performances of SBYR Green 1 real-time, ELlSA and conventional agarose detection methods in detecting nested PCR products were compared. It was found that the real-time PCR was at least 100 times more sensitive than ELlSA detection method with a detection limit of 250 pglpl. The developed assay detects both very virulent and vaccine strains of IBDV but not other RNA viruses such as Newcastle disease virus and infectious bronchitis virus. However, the assay was unable to differentiate the different strains of IBDV. In the subsequent studies, strain-specific primer (match primer) combinations were used for the detection and differentiation of IBDV strains using two steps SYBR Green 1 based real-time PCR. The primers and PCR condition were optimized and validated using both very virulent and vaccine strains. By using the strainspecific primer combinations, specific amplification based on measurement of CT and Tm were detected. In an optimized PCR condition, specific amplification associated with early amplification with CT value between 19 to 28 and Tm between 86 to 88OC meanwhile nonspecific amplification from mismatch primer was associated with late amplification with CT value > 29 and Tm < 82OC or no amplification (CT value 0 and Tm < 82OC). These characteristic CT and Tm values were consistently detected following amplification with 4000 nglul of cDNA. Hence, the differentiation of IBDV strains was based on the detection of CT values whilst detection of Tm was for confirmation of the specific amplification. The detection of Tm value alone was not sufficient to differentiate IBDV strains. Even though the detection limit of the real-time PCR to detect IBDV strains was between 6.6 to 7.7 nglpl, it is recommended that for testing of clinical samples, the cDNA concentrations be maintained between 4000 nglpl to 66 nglpl for PCR amplification, since amplification from insufficient primer-template concentration promote amplification of mismatch PCR product. In this study, it showed for the first time application of SYBR Green 1 based real-time PCR for the detection and differentiation of very virulent and vaccine strains of IBDV. The assay was found to be sensitive, specific, less expensive and has less turn around time compared to the current available diagnostic methods